The Bubble Act New Perspectives from Passage to Repeal and Beyond - Paul, Helen; Di Liberto, Nicholas; Coffman, D`Maris (Palgrave Studies in the History of Finance, 2023)
XXIII, 300 p. 13 illus., 4 illus. in color.